(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This article discusses the gaps in criminal law enforcement related to hoaxes and hate speech in Indonesia’s digital era. The spread of disinformation and misinformation poses a significant challenge to the national legal system, which still struggles to distinguish between freedom of expression and acts classified as criminal offenses. The study focuses on analyzing existing legal provisions, identifying inconsistencies in their application, and examining various factors contributing to the gaps in law enforcement. The findings reveal an imbalance in handling hoax and hate speech cases, where law enforcement is often influenced by political interests, social dynamics, and economic considerations. Based on these findings, the article recommends the need for a reformulation of the legal framework to be more responsive and just, prioritizing the principles of proportionality and contextuality in the practice of criminal law enforcement in the digital age. Artikel ini membahas kesenjangan dalam penegakan hukum pidana terkait hoaks dan ujaran kebencian di Indonesia pada era digital. Penyebaran disinformasi dan misinformasi menjadi tantangan besar bagi sistem hukum nasional, yang masih kesulitan membedakan antara kebebasan berpendapat dan tindakan yang masuk kategori tindak pidana. Kajian ini fokus pada analisis ketentuan hukum yang berlaku, mengidentifikasi inkonsistensi dalam penerapannya, serta menelaah berbagai faktor yang menyebabkan kesenjangan dalam penegakan hukum. Hasil penelitian menunjukkan adanya ketidakseimbangan dalam penanganan kasus hoaks dan ujaran kebencian, di mana penerapan hukum sering dipengaruhi oleh kepentingan politik, dinamika sosial, dan faktor ekonomi. Berdasarkan temuan tersebut, artikel ini merekomendasikan perlunya reformulasi kerangka hukum yang lebih responsif dan adil, dengan mengutamakan prinsip proporsionalitas dan kontekstualitas dalam praktik penegakan hukum pidana di era digital.